Senses and meanings of primary health care academic visions in nursing - Florez-Escobar, Isabel Cristina; Alves-Nascimento, Maria Angela; Contreras-Briceño, José Ivo; Carvajal-Suárez, Lennys Soley (Universidad y Salud, 2024)
Introduction: Primary Health Care (PHC) has acquired different meanings for different people, at specific times and places, which poses important challenges for its understanding. Objective: To analyze the meaning(s) and sense(s) of Primary/Basic Health Care in the academic views on Nursing/Health in the context of undergraduate Nursing courses offered at two public Higher Education Institutions. Materials and methods: Qualitative study with an exploratory approach. Semi-structured interviews and documentary analysis were used as data collection techniques. Results: The senses/meanings of Primary Health Care converge with the population’s gateway to the health system at the first care level and with the first contact of a person with the health service. However, it is still considered as a less important service within the care network. Conclusion: Primary Health Care means a relevant possibility for Nursing/Health care through health promotion and disease prevention actions, with a commitment to respond to most of the population’s health needs.